Negative Effects of SIGIRR on TRAF6 Ubiquitination in Acute Lung Injury In Vitro - Feng Tian; Qiang Lu; Jie Lei; Yunfeng Ni; Nianlin Xie; Daixing Zhong; Guang Yang; Shaokui Si; Tao Jiang (Journal of Immunology Research)
In this study, the effects of single immunoglobin IL-1 receptor-related protein (SIGIRR) on tumor necrosis factor- (TNF-) receptor-associated factor 6 (TRAF6) ubiquitination in acute lung injury (ALI) were evaluated in both alveolar epithelial cells and alveolar macrophage cells in vitro. Our results found that SIGIRR negatively regulated TRAF6 ubiquitination and such SIGIRR inhibition could enhance the TRAF6 expression in both alveolar epithelial cells (AECs) and alveolar macrophage cells (AMCs). SIGIRR knockdown may increase NF-κB activity via TRAF6 regulation by the classical but not the nonclassical NF-κB signaling pathway. Such modulation between TRAF6 and SIGIRR could affect cytokine secretion and exacerbate the immune response; the IL-8, NFKB1, and NFKBIA mRNA levels were reduced after SIGIRR overexpression. The current study reveals the molecular mechanisms of the negative regulatory roles of SIGIRR on the innate immune response related to the LPS/TLR-4 signaling pathway and provides evidence for strategies to clinically treat inflammatory diseases.